Valvular Heart Disease and Pregnancy in the Delivery Room at Yalgado Ouedraogo University Hospital about 12 Cases - Jonas Kologo Koudougou; Rosario Christian Millogo Georges; Salissou Seck Mbaye Mbaye; Aristide Yaméogo Relwendé; Adoko Hermann; Mandi Germain; Bernard Ouedraogo W; Zingué Adolphe; Thiam/Tall Anna; K. Samadoulougou André (Journal of Hypertension and Cardiology, 2022)
This series summarizes 12 pregnancies complicated by valvular heart disease, focusing on intrapartum management, anesthesia choices, and maternal–fetal outcomes in a resource‑limited setting.
Keywords: Heart